Mapping existing research on flushing peripheral vascular catheters: a scoping review protocol - Liping Liu; Peter J Carr; Orlaith Hernon; Jiaxin Deng; Catriona Duggan; Leo R Quinlan; Zina Alfahl (BMJ Open)
Introduction The peripheral vascular catheter (PVC) is the most common intravenous medical device used in hospitals, given it is crucial for the delivery of intravenous therapies. Despite its widespread use, PVC complications such as occlusion, infiltration, extravasation, phlebitis, thrombophlebitis, catheter-related thrombosis and catheter-related bloodstream infection significantly affect patient safety, leading to increased morbidity and healthcare costs. One approach to maintain PVC patency and therefore device longevity is to flush the PVC. This usually involves the use of 5 to 10 mL syringes with normal saline. The evidence on PVC flushing practices is dispersed, making it difficult to draw clear conclusions about current practices and clinical implications. A scoping review is needed to explore and synthesise this evidence systematically and to systematically map the existing research on PVC flushing by assessing the scope, methodologies and outcomes of existing studies.Methods and analysis The review will adhere to the Joanna Briggs Institute (JBI) methodology, using a three-phase search strategy as recommended by JBI and covering the full-time range available in each database. Systematic searches will be conducted across Embase, Web of Science, PubMed, Scopus, and CINAHL; clinical trial registries; and grey literature sources to identify potentially eligible studies published up to May 2024. Following duplicate removal, 3021 records will remain for screening. Two independent reviewers will screen the records and extract data based on the review questions. The reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews, with the results and discussion structured according to the Patterns, Advances, Gaps, Evidence for practice and Research recommendations framework.Ethics and dissemination Ethics approval is not required for this study. The findings will be shared through professional networks, presented at conferences and published in a scientific journal.